Dilatometric analysis of sintering lithium-titanium-zinc ferrite with ZrO2 additive; Journal of Thermal Analysis and Calorimetry; Vol. XXX, iss. X - Nikolaeva S. A. Svetlana Andreevna; Lysenko E. N. Elena Nikolaevna; Nikolaev E. V. Evgeny Vladimirovich; Surzhikov A. P. Anatoly Petrovich (2021, 2021)
Title screen